A Li–Li4Ti5O12 Composite Anode for Reducing Interfacial Resistance of Solid‐State Batteries - Chencheng Cao; Yijun Zhong; Bingbing Chen; Rui Cai; Zongping Shao (Small Structures, 2023)
The high energy density and stability of solid‐state lithium batteries (SSBs) have garnered attention. Garnet electrolytes are widely explored in SSBs due to their huge electrochemical potential window, high effective ionic conductivity, and reasonable production cost. However, the electrochemical stability of a metallic lithium anode and a garnet electrolyte pose obstacles to the widespread use of garnet‐based SSBs. To remedy these problems, Li4Ti5O12 (LTO) is added to the metallic lithium anode. With superior wettability on the garnet electrolyte compared to pure metallic Li, Li–LTO is a more desirable electrolyte. Increased wettability between the garnet electrolyte and Li–LTO composite is responsible for the larger absolute value of the interface formation energy found in the first principal density‐functional theory calculation. Since the interface resistance between the Li–LTO composite anodes (25 Ω cm2) and the Li metal (270 Ω cm2) is much lower, Li dendrite development is effectively suppressed. An all‐lithium battery with a Li–LTO anode and a LiFePO4 cathode shows excellent capacity retention of 95% after 450 cycles. This discovery may serve as inspiration for future efforts to create a metallic Li‐containing anode for lithium batteries and other functional LTO‐based composites.